Assessment of in vivo degradation profiles of hyaluronic acid hydrogels using temporal evolution of chemical exchange saturation transfer (CEST) MRI. (September 2018) - Shazeeb, Mohammed Salman; Corazzini, Rubina; Konowicz, Paul A.; Fogle, Robert; Bangari, Dinesh S.; Johnson, Jennifer; Ying, Xiaoyou; Dhal, Pradeep K.
Abstract: Hyaluronic acid (HA) hydrogels have found a wide range of applications in biomedicine: regenerative medicine to drug delivery applications. In vivo quantitative assessment of these hydrogels using magnetic resonance imaging (MRI) provides an effective, accurate, safe, and non-invasive translational approach to assess the biodegradability of HA hydrogels. Chemical exchange saturation transfer (CEST) is an MRI contrast enhancement technique that overcomes the concentration limitation of other techniques like magnetic resonance spectroscopy (MRS) by detecting metabolites at up to two orders of magnitude or higher. In this study, HA hydrogels were synthesized based on different crosslinking agents and assessed using CEST MRI to investigate the in vivo degradation profiles of these gels in a mouse subcutaneous injection model over a three-month period. Nature of crosslinking agents was found to influence their degradation profiles. Since CEST MRI provides a unique chemical signature to visualize HA hydrogels, our studies proved that this technique could be used as a guide in the hydrogel optimization process for drug delivery and regenerative medicine applications.